Experience and Enlightenment of Japan's Emergency Power Supply Guarantee Mechanism. Issue 1 (March 2021) - Han, Zhang; Song, Xue; Li, Ma; Xiaoxuan, Zhang
Abstract: Japan is a country prone to natural disasters such as earthquakes, tsunamis, and typhoons. Electricity is the key material basis for production, life and emergency management, so the reliability and stability of its supply is an important content of Japan's disaster protection. In recent years, people have paid more and more attention to maintaining a normal and independent life even after the power and natural gas infrastructure has stopped. Therefore, the concept and practice of emergency power supply have been circulated and widely implemented in Japan for a long time. This paper summarizes the concepts, legal standards, development history, main methods, work of power grid companies, development trends, etc. of emergency power supply in Japan, and provides relevant experience and inspiration for the development of emergency power supply in China.